Menyeimbangkan Peran Ganda: Tantangan dan Strategi Koping Mahasiswa Khaddam dalam Menyelesaikan Skripsi - Mar’ah Zamratin Fuadah; Bradhiansyah TriSuryanto (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This study aims to explore the experiences of Khaddam students in balancing their religious service responsibilities with academic demands, particularly in completing their undergraduate thesis. The research focuses on the challenges faced by khaddam students and the strategies they employ. This study employs a qualitative phenomenological approach. Data were collected through in-depth interviews with khaddam students currently working on their undergraduate thesis to understand their interpretations and management of these two roles. The findings indicate that khaddam students face role conflict, time constraints, and psychological pressure that affect their ability to complete their final projects. However, they demonstrate high resilience, adaptive coping strategies, and strong motivation rooted in religious values. Social support and time management skills are crucial factors in helping them effectively balance these two roles. This study underscores the complexity of balancing religious commitments with academic demands, as well as the importance of institutional support in fostering the academic success of khaddam students.